Electromyographic study in Erector spinae, Rectus abdominis, Glutaeous maximus and Rectus femuris muscles, in standing and static posture with load on hands - Sgobbi de Faria, C. R.; Berzin, F. (Medimond S R L, 2005)
Observe the loads associates application with in position of body, in the static or dynamic postures. Methods: the electromyographic study in erector spinae, rectus abdominis, glutaeous maximus and rectus femoris muscles was accomplished in female volunteers from 18 have 27 years old, previously selected. The muscles electric activities was gotten with surface electrodes, in standing and static posture, with the parallels and horizontal upper limbs with load on their hands. Conclusion: In this study it was clearly observed influence of the load and distance there is over studied musculature associated with standing erect posture.